Effect of physical rehabilitation on insomnia among cancer patients undergoing chemotherapy (Latakia University Journal -Medical Sciences Series, 2024)
Insomnia is widely spread among cancer patients undergoing chemotherapy, which may exacerbate their pre-existing health issues. The study sheds light on the role of physical therapy programs in managing insomnia. The current quasi-experimental study aimed to determine the impact of physical rehabilitation on insomnia of cancer patients undergoing chemotherapy. The study included 60 patients at the chemotherapy and radiation treatment center at Tishreen University Hospital in Latakia. They were selected using appropriate sampling methods and non-randomly divided into two groups: an experimental group of 30 patients receiving physical rehabilitation and a control group of 30 patients following the hospital's routine care. Data was collected using the Athena Insomnia Scale AIS. The study found that the majority of cancer patients undergoing chemotherapy suffer from moderate to severe levels of insomnia. Physical therapy was shown to effectively alleviate their insomnia levels. The study recommended including insomnia assessment as a routine part of the nursing care plan for cancer patients, along with implementing the physical therapy outlined in this study to reduce insomnia in chemotherapy-treated cancer patients.